2008
DOI: 10.1038/ismej.2008.27
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread distribution of proteorhodopsins in freshwater and brackish ecosystems

Abstract: Proteorhodopsins (PRs) are light-driven proton pumps that have been found in a variety of marine environments. The goal of this study was to search for PR presence in different freshwater and brackish environments and to explore the diversity of non-marine PR protein. Here, we show that PRs exist in distinctly different aquatic environments, ranging from clear water lakes to peat lakes and in the Baltic Sea. Some of the PRs observed in this study formed unique clades that were not previously observed in marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 30 publications
5
94
0
Order By: Relevance
“…The gene encoding the first discovered member of this group was detected in the genome sequence of an uncultured γ-proteobacterium from oceanic waters (5). Since then, PRs have turned out to be highly abundant in the oceans (6)(7)(8)(9), and organisms containing them, including a cyanobacterium (10) can be found in many other habitats as well (7,(11)(12)(13). In vivo experiments have shown that pumping of protons by PR can lead to increases in growth rate under nutrient-limited conditions (6,14,15), production of ATP (16), increased fixation of CO 2 (6,17), and/or survival under starvation or stress conditions (16,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding the first discovered member of this group was detected in the genome sequence of an uncultured γ-proteobacterium from oceanic waters (5). Since then, PRs have turned out to be highly abundant in the oceans (6)(7)(8)(9), and organisms containing them, including a cyanobacterium (10) can be found in many other habitats as well (7,(11)(12)(13). In vivo experiments have shown that pumping of protons by PR can lead to increases in growth rate under nutrient-limited conditions (6,14,15), production of ATP (16), increased fixation of CO 2 (6,17), and/or survival under starvation or stress conditions (16,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ActR, proteorhodopsin-encoding gene fragments affiliated with proteobacterial and bacteroidetes sequences (Supplementary Table S2) were also amplified from the Great Lakes Superior and Erie. Several recent studies highlight the broad taxonomic and ecological distribution of microbial rhodopsin genes in diverse aquatic environments (Rusch et al, 2007;Atamna-Ismaeel et al, 2008;Sharma et al, 2008), suggesting they are important in the adaptation of microbes to life on the earth's surface. However, exploratory studies such as ours can only provide insight into sequence diversity, generating fundamental questions regarding rhodopsin function and its impact at both cellular and ecosystem levels.…”
Section: Isolate Mwh-uga1 Encodes An Lg1-actrmentioning
confidence: 99%
“…Degenerated PR primers were modified from Atamna-Ismaeel et al (2008) and Koh et al (2010), with an expected PCR product size of B350 bp. An additional reverse primer (PR-R4) was created after in silico testing with the Fuzznuc web application (http://emboss.bioinformatics.nl/cgi-bin/emboss/ fuzznuc).…”
Section: Pr Primers and Pcr Amplificationmentioning
confidence: 99%